Gagal Ginjal Kronik Hemodialisis dengan Kadar Eritropoietin dan Hemoglobin Normal: Laporan Kasus - Amudi, Tulus; Palar, Stella (Medical Scope Journal, 2021)
Abstract: Generally, chronic kidney disease (CKD) is associated with anemia due to decrease of erythropoietin that plays an important role in erythropoiesis. We reported a patient, 61-year-old male, suffered from chronic hemodialysis kidney disease with coinfection of viral hepatitis C, albeit, had normal hemoglobin and erythropoietin levels. The patient was diagnosed as CKD in March 2014 with laboratory results, as follows: hemoglobin (Hb) 9.9 g/dl; ureum 223 mg/dl; creatinine 7.5 mg/dl, and was confirmed with ultrasonography. The patient underwent hemodialysis and was treated with erythropoiesis stimulating agent (ESA) for the first time in April 2014. The last ESA was given in June 2015 and the laboratory results were serum iron 61 µg/dl, total iron binding capacity (TIBC) 173 µg/dl, ferritin 1431 ng/ml, and the qualitative anti HCV test was reactive. Afterwards, the patient was not treated with ESA anymore since his Hb level was normal without ESA or blood transfusion. Moreover, the erythropoietin (EPO) level was tested in December 2018 resulted within normal level. Until now, the patient is still undergoing hemodialysis without ESA or transfusion. This is a rare condition, and there is still no certain pathophysiology to explain. It is assumed that the mechanism is related to hepatitis C infection that stimulates the hepatocyte regeneration, therefore, the cells produce endogen erythropoietin resulting in increased Hb level.Keywords: chronic kidney disease (CKD), erythropoietin and hemoglobin level Abstrak: Umumnya penyakit ginjal kronik (PGK) disertai dengan anemia akibat penurunan eritropoietin yang berperan penting dalam proses eritropoiesis. Kami melaporkan kasus seorang laki-laki 61 tahun dengan PGK hemodialisis disertai ko-infeksi hepatitis C namun dengan kadar hemoglobin dan eritropoietin normal. Pasien dinyatakan PGK sejak Maret 2014 dengan kadar hemoglobin (Hb) 9,9 g/dL; ureum 223 mg/dl; kreatinin 7,5 mg/dl, dan didukung oleh hasil ultrasonografi. Pasien diberikan hemodialisis dan terapi ESA pertama kali pada bulan April 2014. Terapi ESA terakhir diberikan pada bulan Juni 2015 dengan hasil serum iron 61 µg/dl, total iron binding capacity (TIBC) 173 µg/dl, feritin 1431 ng/ml, dan anti HCV kualitatif reaktif, Setelah itu pasien tidak mendapat terapi ESA lagi karena pada pemeriksaan laboratorium ditemukan kadar hemoglobin normal tanpa terapi ESA atau transfusi darah. Pemeriksaan kadar eritropoietin (EPO) pada bulan Desember 2018 mendapatkan hasil 16 mIU/ml (nilai normal 2,6-18,5 mIU/ml). Hingga saat ini pasien masih rutin menjalani hemodialisis dan tidak pernah mendapat terapi ESA atau transfusi darah. Keadaan tersebut jarang ditemukan, dan tidak ada patofisologi yang pasti untuk menjelaskan penyebab keadaan tersebut. Mekanisme keadaan ini dikaitkan dengan infeksi hepatitis C yang merangsang regenerasi hepatosit, sehingga sel-sel tersebut menghasilkan hormon ertiropoietin endogen, dengan hasil akhir ialah peningkatan hemoglobin.Kata kunci: penyakit ginjal kronik (PGK), kadar eritropoietin dan hemoglobin